2022
DOI: 10.3389/fphar.2022.893244
|View full text |Cite
|
Sign up to set email alerts
|

Yuan-Zhi decoction in the treatment of Alzheimer’s disease: An integrated approach based on chemical profiling, network pharmacology, molecular docking and experimental evaluation

Abstract: Yuan-Zhi Decoction (YZD) is a traditional Chinese medical formulation with demonstrated clinical benefits in Alzheimer’s disease (AD). We used liquid chromatography coupled with mass spectrometry to identify 27 unique chemical components of YZD. Analyzing these using network pharmacology and molecular docking models identified 34 potential interacting molecular targets involved in 26 biochemical pathways. When tested in an animal model of AD, the APP/PS1 transgenic mice showed measurable improvements in spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…The ingredients in PF were obtained through the symMap database, the Traditional Chinese Medicines Integrated Database (TCMID), and the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP) [ 17 ]. The chemicals with oral bioavailability ≥30% and with violations of no more than two items in the five criteria of drug-likeness were screened out as competent pharmacological compounds for further study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ingredients in PF were obtained through the symMap database, the Traditional Chinese Medicines Integrated Database (TCMID), and the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP) [ 17 ]. The chemicals with oral bioavailability ≥30% and with violations of no more than two items in the five criteria of drug-likeness were screened out as competent pharmacological compounds for further study.…”
Section: Methodsmentioning
confidence: 99%
“…Network-based topological analysis tools, particularly dynamic analysis tools, have great potential for finding and developing multitarget drugs and identifying alternative targets [ 16 ]. Molecular docking is a computational simulation to explore ligand conformations adopted within receptor binding sites during intermolecular recognition [ 17 ]. Recently, it has also drawn great attention in the field of plant research [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cytoHubba plugin tool was then used to analyze the network, and top ten genes were selected based on their degree value. According to results of analysis TNF (28), IL6 (28), EGFR (24), MMP9 (23), HSP90AA1 (23), VEGFA (22), TP53 (20), AKT1 (20), CTNNB1 (18), and CCL2 (17) were found to be the top ten target genes. Comparison of PPI analysis with enrichment analysis reveals that among the top 10 genes TNF, IL6, AKT1, and CCL2 were found to be the main target genes that may contribute to the anti-inflammatory potential of PFE.…”
Section: Construction Of a Protein−protein Interaction Networkmentioning
confidence: 99%
“…Network pharmacology is an emerging technique for understanding multicomponent drugs’ mechanism of action. Its basic idea is to maximize treatment options based on a biological network comprising disease characteristics, bioactive agents, and therapeutic targets that are all linked . Bioinformatics and systems biology advances are making network pharmacology a viable approach for identifying active compounds and elucidating the underlying pharmacological mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Polygalae radix (PR), the dried root of Polygala tenuifolia Willd. or Polygala sibiria L., is a well-known traditional Chinese medicine that has the effect of tranquilizing the mind, improving intelligence, and restoring normal coordination between the heart and kidneys, and this medicine is widely used for the treatment of insomnia, dreaminess, palpitations, and neurasthenia in clinic [ 10 ] in the form of Kai-Xin-San, Yuan-Zhi decoction, or Anshendingzhi decoction [ 11 , 12 , 13 ]. Modern pharmacological studies have also shown that PR has beneficial antidepressant, sedative, anti-aging, neuroprotective, intelligence, and immune system effects [ 14 ].…”
Section: Introductionmentioning
confidence: 99%